Índice sustentável de bem-estar econômico: uma proposta de mesuração para os municípios paulistas - Silva, Jonathas de Melo Cristovão (Universidade Federal de São Carlos, 2014)
The objective of this research is incorporate environmental conditions in a synthetic index of well-being for the counties beyond traditional dimensions of income, education and health in order to contribute to the diagnosis of the quality of life. Among the many challenges presented to policymakers, one of the applicants is a relative scarcity of public resources to meet a growing demand for goods and services. Another set of challenges is the difficulty of making more accurate diagnoses of problems and needs of the population, making the choice of priorities for action no trivial task. Analytical tools that can assist planning and monitoring of public policies are essential to establish alternatives for expanding the economic and social well-being, integrating economic growth and environmental sustainability. To meet the proposed goal, this work uses MIQL-M - Multidimensional Index of Quality of Life, a multidimensional index composed by the capabilities, concepted by Sen, still incorporating environmental sustainability indicators present in IAA- Index Environmental Assessment, established by the State Secretariat of Environment of São Paulo. Obtained a new index of well-being, perform a comparison of the systems of the municipalities according to the relative position obtained with and without the environmental variable. The main results show that the best municipalities assessed by modified MIQL-M did not show good results when environmental sustainability is considered. The districts with low quality of life were more dispersed throughout the territory and more concentrated in the east and south of the state. The municipalities that have improved their positions when the environmental factor is considered were more concentrated in the area of environmental preservation, and the relative improvement did not guarantee high degree of development since the evaluation considers other socioeconomic factors. Those who have lost positions in the ranking were located in regions where industrial dynamics is strongly present in the state. However, the global Moran's I test rejects the hypothesis that municipalities with high industrial participation are influencing the quality of life of neighboring regions due to spatial proximity.
-
Keywords: economia do bem-estar; sustentabilidade - índices; economia regional; bem-estar; qualidade de Vida; sustentabilidade; economia regional; weel-being, quality of life, sustainability, regional economy; CIENCIAS SOCIAIS APLICADAS::ECONOMIA